Differentiate a Health and Sick of Mango Leaves Using YOLOv4 - Prya Artha Widjaja; Jose Ryu Leonesta (Formosa Journal of Science and Technology, 2023)
Healthy plants will provide good results for farmers. As in humans, plants can also be affected by diseases that can result in death or crop failure. This study uses the object recognition method, namely YOLO (You Only Look Once) version 4 to determine whether a plant is categorized as sick or healthy. The data used in this research is secondary data. The results obtained were in line with expectations, namely being able to distinguish between healthy and diseased leaves.